Additive manufacturing of multi-morphology graded titanium scaffolds for bone implant applications. (10th March 2023) - Yu, Aihua; Zhang, Ce; Xu, Wei; Zhang, Yun; Tian, Shiwei; Liu, Bowen; Zhang, Jiazhen; He, Anrui; Su, Bo; Lu, Xin
Highlights: Multi-morphology graded Ti scaffolds with different porosities were designed and characterized systematically. Hybridized gradients design enhances mechanical and biological performances of scaffolds simultaneously. Higher strength, appropriate permeability and elastic modulus, and excellent cytocompatibility make PG50 an promising orthopedic implant. Abstract: Porous Titanium scaffolds have attracted widespread attention as bone implants for avoiding the stress shielding effect and promoting bone-in-growth. In this study, multi-morphology graded scaffolds hybridized by Primitive and Gyroid structures with porosity of 50, 60, and 70% were designed (denoted as PG50, PG60, and PG70, respectively) and fabricated by selective laser melting. The simulation results showed that the maximum von–Mises stress of hybridized scaffolds increased from 504.22 to 884.24 MPa with porosity. The permeability and average pore size of multi-morphology PG50, PG60, and PG70 were in the range of 3.58 × 10 –9 –5.50 × 10 –9  m 2 and 568.1–758.4 μm, respectively. The microstructure of multi-morphology graded scaffolds consisted of a fully martensitic α′ phase. Tested permeabilities of PG50 and PG60 were 3.27 × 10 –9 and 4.35 × 10 –9  m 2, respectively, which were within the range of human bone (0.01–12.1 × 10 –9  m 2 ). Elastic modulus and compressive yield strength of PG50 and PG60 ranged within 5.93–9.86 and 180.06–257.08 MPa, respectively. Therein, the PG50 not only exhibited a similar elastic modulus compared to human cortical bone (10.1 GPa) but also had higher strength (257.08 vs 131 MPa). The results of in vitro biocompatibility assay showed that PG50 and PG60 have better cytocompatibility than mono-morphology scaffolds with the same porosity. Taken together, PG50 is promising to be used for the restoration of bone defects due to its excellent mechanical properties, appropriate permeability, and good cytocompatibility.